99.0k views
1 vote
Y = 4x+1 y=x^2 + 2x - 2 A.6,2 B. 2,6 C. -6,2 D. -6,-2

User Miles D
by
5.6k points

1 Answer

4 votes

Answer:

The solution is (3,13) and (-1,-3). So none of the mentioned options is correct.

Explanation:

Given that


y = 4x + 1  (i)


y = x^2 + 2x -2 (ii)

Now, by susbstituting the value of 'y' from equation i to equation ii, we get


4x+1=x^2 + 2x -2


0=x^2 + 2x -2-4x-1


0=x^2 + (2x -4x) +(-2-1)


0=x^2 + (-2x) +(-3)


0=x^2 -2x -3


x^2 -2x -3 = 0 (iii)

Now by factorization, equation iii can be written as


x^2 -3x +x -3 = 0


x(x -3) + 1(x -3) = 0


(x -3)(x +1) = 0

x = 3 and x = -1

By putting the values of x in equation i, we get

y = 4(3) + 1

y = 12 +1

y = 13

and

y = 4(-1) + 1

y = -4 +1

y = -3

Therefore, the solution is (3,13) and (-1,-3). So none of the mentioned options is correct.

User Blankmaker
by
5.9k points